2005
DOI: 10.1007/s10822-005-9006-2
|View full text |Cite
|
Sign up to set email alerts
|

Topological side-chain classification of β-turns: Ideal motifs for peptidomimetic development

Abstract: Beta-turns are important topological motifs for biological recognition of proteins and peptides. Organic molecules that sample the side chain positions of beta-turns have shown broad binding capacity to multiple different receptors, for example benzodiazepines. Beta-turns have traditionally been classified into various types based on the backbone dihedral angles (phi2, psi2, phi3 and psi3). Indeed, 57-68% of beta-turns are currently classified into 8 different backbone families (Type I, Type II, Type I', Type … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 62 publications
(83 reference statements)
0
19
0
Order By: Relevance
“…One-to-one correspondence between a particular b-turn type and a particular cluster requires that the primary composition of a particular cluster to be of a particular b-turn type and the primary composition of the b-turn type to be of the particular cluster. We have previously argued that particular b-turn types can have more than one peak or mode structures and that members of different b-turn types can have similar side-chain shape [70]. Therefore, it was not unexpected that there was no one-to-one correspondence between b-turn types, which were classified based on the backbone dihedral angles and the clusters found here, which were classified based on the conformations of the side-chain.…”
Section: Relationship Between the 39 Clustersmentioning
confidence: 60%
“…One-to-one correspondence between a particular b-turn type and a particular cluster requires that the primary composition of a particular cluster to be of a particular b-turn type and the primary composition of the b-turn type to be of the particular cluster. We have previously argued that particular b-turn types can have more than one peak or mode structures and that members of different b-turn types can have similar side-chain shape [70]. Therefore, it was not unexpected that there was no one-to-one correspondence between b-turn types, which were classified based on the backbone dihedral angles and the clusters found here, which were classified based on the conformations of the side-chain.…”
Section: Relationship Between the 39 Clustersmentioning
confidence: 60%
“…37 The ability of our CTPs NMR conformation to mimic reverse turns was established by how well the NMR experimental structure had bonds overlapping the nine sets of four vectors established by Tran et al 37 as representative of reverse-turn Ca-Cb bonds. It was found that overlapping a Ca-Cb vector of a Tran et al cluster with a CÀ ÀH bond on a CTP gave an undesired biased overlap compared to overlapping a CÀ ÀC bond in the CTP.…”
Section: Overlap Of Structures With Reverse-turn Classes From Pdbmentioning
confidence: 93%
“…It has been shown that reverse turns in the same classical-turn type can differ in the orientation of their side chains. 37 Because reverse turns are usually recognized in biological systems by their relative side-chain orientation and not direct interactions with their backbones, the classical classification method is not optimal. Recently, Tran et al 37 have elucidated nine classes of orientations of the four consecutive Ca-Cb bonds of a reverse turn that represent the vast majority (*90%) of reverse turns found in the PDB.…”
Section: Reverse-turn Mimetic Screenmentioning
confidence: 99%
See 1 more Smart Citation
“…The distance between the C-alphas of Gly112 and Tyr115 and the distance between the carbonyl oxygen of Gly112 and amide hydrogen of Tyr115 were recorded ( Figure 14) at each time step after initial equilibration similar to the studies by Takeuchi and Marshall 126 on reverse-turn propensity. The virtual dihedral angle defined by the four C-alpha carbons of the reverse turn, as suggested by Tran et al, 127 of Gly112, Asn113, Pro114, and Tyr115 was also monitored as shown in Figure 14.…”
Section: Simulations Of Chimeric Rnasementioning
confidence: 99%